Rational design of a triple-type HPV53/56/66 vaccine with one preferable base particle incorporating two identified immunodominant sites - Ciying Qian; Jie Chen; Yurou Yang; Yihan Lu; Tianyu Ren; Yanan Jiang; Yang Huang; Xin Chi; Shuyue Zhang; Chengzong Zhang; Kewei Li; Jingjia Shen; et al. (Journal of Nanobiotechnology)
Abstract The numerous high-risk carcinogenic types of human papillomavirus (HR-HPV) that lack vaccine protection underscore the urgent need to develop broader-spectrum HPV vaccines. This study addresses this need by focusing on HR-HPV types 53, 56, and 66, which are not currently targeted by existing vaccines. It introduces an effective method for their soluble expression, as well as that of their mutants, within an Escherichia coli expression system. Through strategic homologous loop swapping among HPV53, HPV56, and HPV66, we designed twenty double-type chimeric molecules. Comprehensive evaluations identified unique dominant immunogenic loops for each type: the FG loop for HPV53, the HI loop for HPV56, and the DE loop for HPV66, with HPV66 emerging as the optimal chimeric backbone virus-like particle (VLP). By incorporating two identified immunodominant sites into the preferable base particle, the study constructed a triple-type chimera H66-56HI-53FG, which could efficiently self-assemble into VLPs in vitro that closely resembled the wild-type HPV66 VLP and, induced balanced triple-type neutralization titers (~ 3 log unites), as contrast to none observable HPV53 neutralization titer and lower HPV56 titer elicited by the immunization of the wild-type HPV66 alone. This research outlines an amenable way to simultaneously identify immunodominant sites and their preferable particle base context for cross-type vaccine design, thereby offering a paradigm as extending antigenic variety in single particle to broaden vaccine protection coverage. Graphical Abstract